The Relationship Between Strap Use and Classification Score in Elite Wheelchair Basketball Players - Giacomo Farì; Francesco Quarta; Sara Clelia Longo; Fernando Zappile; Laura Masiero; Giustino Varrassi; Andrea Bernetti (Sports)
Wheelchair basketball (WB) grants important benefits for people with disabilities but also presents a relevant risk of injury. Wheelchair straps are restraint devices that can improve safety and performance, but limited research has explored their use in WB. This study aims to analyze the use of different types of straps among professional WB players, according to classification score. A cross-sectional study was conducted through an online survey. Participants were divided into two groups based on classification score: low-point players (LPPs; 1.0–2.5), who have greater physical impairment, and high-point players (HPPs; 3.0–4.5), who have lower physical impairment. A total of 82 WB players participated (43 LPPs; 39 HPPs). The Chi-squared test was used to compare variables between groups. Significant differences emerged: chest (p = 0.036), abdominal (p = 0.036), and foot (p = 0.016) straps were more frequently used by LPPs, while thigh (p = 0.020) and leg (p = 0.050) straps were more common among HPPs. No significant difference was found for pelvic strap. Straps used in WB vary with classification score, reflecting the influence of functional ability. These findings offer insights into individualized wheelchair setup and classification procedures. Further studies are needed to expand knowledge on this topic.